Dimensional stabilization of 55%SiCp/Al composites - CUI Yan; LI Pengwei; LI Shuo; CAO Leigang; YANG Yue; LIU Yuan (Cailiao gongcheng)
High volume fraction SiCp/Al composites characterized by high modulus and low expansion have great application potential in the field of aerospace precision instruments. In this application scenario， it is necessary to deepen the study of the dimensional stability of the materials and further improve the precision stability of components. Three kinds of SiC particle-reinforced high volume （55%） aluminum matrix composites with the average particle size （D50） of 14， 76 μm， and gradation of 14 μm and 76 μm are treated with different dimensional stabilization treatments， such as the solid solution aging， the thermal-cold cycling treatment with different temperature parameters after the solid solution， the thermal-cold cycling treatment， etc. After the treatment， the dimensional stability of the samples is tested with the control samples for five times at a low temperature of 180 ℃ thermal loading environment. The results show that compared with the 14 μm particle-reinforced samples， the 76 μm particle-reinforced samples and the gradation of 14 μm and 76 μm particle-reinforced samples show better dimensional stability， the size change rate （dV/V） of the control samples can be stabilized at about 1×10-3. Among the five dimensional stabilization treatment regimes， the effect of -196-191 ℃ （4 times） thermal-cold cycling treatment after the solid solution is the most significant， the size change rate （dV/V） of the samples after this treatment can be stabilized at 10-4 orders of magnitude. According to the comparison of X-ray diffraction patterns， the thermal-cold cycling treatment after the solid solution can promote the precipitation of the strengthening phase of Al2Cu significantly.